Inhibition of myostatin in mice improves insulin sensitivity via irisin-mediated cross talk between muscle and adipose tissues - Dong, Jiangling (Int J Obes (Lond), 2015)
BACKGROUND/OBJECTIVE: In mice, a high fat diet (HFD) induces obesity, insulin resistance and myostatin production. We tested whether inhibition of myostatin in mice can reverse these HFD-induced abnormalities. SUBJECTS/METHODS: C57BL/6 mice were fed a HFD for 16 weeks including the final 4 weeks some mice were treated with an anti-myostatin peptibody. Body composition, the respiratory exchange ratio plus glucose and insulin tolerance tests were examined. Myostatin knock down in C2C12 cells was performed using ShRNA lentivirus. Adipose tissue-derived stem cells were cultured to measure their reponses to conditioned media from C2C12 cells lacking myostatin, or to recombinant myostatin or Irisin. Isolated peritoneal macrophages were treated with myostatin or Irisin to determine if myostatin or Irisin induce inflammatory mechanisms. RESULTS: In HFD-fed mice, peptibody treatment stimulated muscle growth and improved insulin resistance. The improved glucose and insulin tolerances were confirmed when we found increased muscle expression of p-Akt and the glucose transporter, Glut4. In mice fed the HFD, the peptibody suppressed macrophage infiltration and the expression of proinflammatory cytokines in both muscle and adipocytes. Inhibition of myostatin caused the conversion of white (WAT) to brown adipose tissue (BAT) while stimulating fatty acid oxidation and increasing energy expenditure. The related mechanism is a muscle-to-fat cross talk mediated by Irisin. Myostatin inhibition increased PGC-1α expression and Irisin production in muscle. Irisin then stimulated WAT browning. Irisin also suppresses inflammation and stimulates macrophage polarization from M1 to M2 types. CONCUSION: these results uncover a metabolic pathway from an increase in myostatin that suppresses Irisin leading to activation of inflammatory cytokines and insulin resistance. Thus, myostatin is a potential therapeutic target to treat insulin resistance of type II diabetes as well as the shortage of brown/beige fat in obesity.